A risk de-aggregation framework that relates community resilience goals to building performance objectivess. Issue 1 (10th June 2016) - Lin, Peihui; Wang, Naiyu; Ellingwood, Bruce R.
Abstract: Resilience is often regarded as an attribute of communities rather than of individual buildings, bridges, and other civil infrastructure facilities. Previous research to support development of resilient infrastructure has considered, for the most part, actions and policies to achieve resilience objectives at the community level. While it is clear that a community cannot be resilient without resilient individual facilities, few attempts have been made to relate the performance criteria for individual facilities to community resilience goals in a quantitative manner. This paper presents a method for relating risk-informed performance criteria for individual buildings exposed to extreme hazards to broader community resilience objectives and illustrates the application of the method to two residential building inventories. The paper demonstrates the feasibility of de-aggregating community resilience goals to obtain design performance objectives for individual facilities and thereby relating community goals to requirements in codes and standards that govern design of buildings and other structures.